Cultural Ecology: Land Ownership of Hmong Ethnicity in Houi Han Community Chiang Rai - Pusara, Adisorn (Journal of International Studies, Prince of Songkla University, 2025)
This research was a phenomenological qualitative study, aiming to apply cultural ecology theory to explain land ownership among the Hmong ethnic group in Houi Han Community, Wiang Kaen District, Chiang Rai Province. The key informants consisted of five community cultural elders and five senior members from Sae families. The quality of the research was validated by the village leader, who served as an academic expert. The results revealed that the Hmong ethnic group selected areas for community settlement based on ancestral beliefs, suitable geographical features, and settlement prohibitions. Additionally, settlement decisions were influenced by mutual agreements between the Thai government and the Thailand Collaboration Development Group. Land ownership traditionally belonged to the individual who pioneered the area. The transfer of land ownership was passed to the son as the successor of the Sae family; however, daughters did not have inheritance rights. Land tenure stability was supported by the Thai government through the provision of public services although ownership was granted without formal land title documents. Land ownership disputes were managed through a restorative justice process. Changes in land tenure patterns emerged with the introduction of land trading, driven by rapid population growth, the influx of Hmong refugees from United Nations camps, and government efforts to reclaim forest areas. Land trading within the community was permitted but required approval from the village committee when transactions involved individuals from outside the community.